2002
DOI: 10.1557/proc-754-cc11.8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phases of Glass-Forming Mixtures

Abstract: We compare the potential energy at zero temperature of a range of crystal structures for a glass-forming binary mixture of Lennard-Jones particles. The lowest energy ordered state consists of coexisting phases of a single component face centered cubic structure and an equimolar cesium chloride structure. An infinite number of layered crystal structures are identified with energies close to this groundstate. We demonstrate that the finite size increase of the energy of the coexisting crystal with incoherent int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The eutectic of these two crystal phases is located around 26% B particles, but interestingly there is a narrow region around the eutectic in which the bipyramidal orthorhombic PuBr 3 structure is the thermodynamically stable phase. We also studied the Al 2 Cu, Fe 3 C, and Ni 3 P structures shown by Fernández and Harrowell to be of low energy at T = 0 and p = 0 [37], but found that their melting temperatures are all lower, compare Fig. 3 and Table I.…”
mentioning
confidence: 94%
“…The eutectic of these two crystal phases is located around 26% B particles, but interestingly there is a narrow region around the eutectic in which the bipyramidal orthorhombic PuBr 3 structure is the thermodynamically stable phase. We also studied the Al 2 Cu, Fe 3 C, and Ni 3 P structures shown by Fernández and Harrowell to be of low energy at T = 0 and p = 0 [37], but found that their melting temperatures are all lower, compare Fig. 3 and Table I.…”
mentioning
confidence: 94%